Disrupted thalamic resting-state functional networks in schizophrenia - Wang, Hsiao-Lan Sharon; Rau, Chi-Lun; Li, Yu-Mei; Chen, Ya-Ping; Yu, Rongjun (Frontiers in Behavioral Neuroscience, 2015)
The thalamus plays a key role in filtering or gating information and has extensive interconnectivity with other brain regions. Recent studies provide evidence of thalamus abnormality in schizophrenia, but the resting functional networks of the thalamus in schizophrenia is as yet unclear. We characterize the thalamic resting-state networks (RSNs) in 72 patients with schizophrenia and 73 healthy controls, using a standard seed-based whole-brain correlation. In comparison with controls, patients exhibited enhance thalamic connectivity with bilateral precentral gyrus, dorsal medial frontal gyrus, and middle occipital gyrus. Reduced thalamic connectivity in schizophrenia was found in bilateral superior frontal gyrus, anterior cingualte cortex, and inferior parietal lobe. Our findings question the "disconnectivity model" of schizophrenia by showing the over-connected thalamic network during resting state in schizophrenia and highlight the thalamus as a key hub in the schizophrenic network abnormality.